Respuesta :
Answer:
3
Step-by-step explanation:
12 x 2 = 24
24 + 2 = 26
26 + (-3) = 23
23 - 16 = 7
7 - 4 = 3
Answer:
3
Step-by-step explanation:
you have to do what is in parenthesis so you would add 2 and 12 and get 14 then you would drop everything down and then your problem should look like this:-3(14 times 2)-16-4 then you would need to multiply 14 and 2 and you would get 26.your problem should now look like this -3+26-16-4,then you add negative 3 and 26 and you would get 23-16-4.then you subtract 16 from 26 and then you get 7 so now your problem is 7-4 and you would get 3.
-3+(2+12times2)-16-4
-3+(14times2)-16-4
-3+26-16-4
23-16-4
7-4
3